2020
DOI: 10.1186/s12889-020-09925-6
|View full text |Cite
|
Sign up to set email alerts
|

Advancing universal health coverage in China and Vietnam: lessons for other countries

Abstract: Background China and Vietnam have made impressive progress towards universal health coverage (UHC) through government-led health insurance reforms. We compared the different pathways used to achieve UHC, to identify the lessons other countries can learn from China and Vietnam. Methods This was a mixed method study which included a literature review, in-depth interviews and secondary data analysis. We conducted a literature search in English and Chinese databases, and reviewed policy documents from internal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 17 publications
(16 reference statements)
0
31
0
Order By: Relevance
“…The results show that UEBMI, URBMI, and NRCMS had higher healthcare utilisation and experienced faster increases than uninsured respondents between 2008 and 2018. This implies that the rapid expansion of UEBMI, URBMI, and NRCMS with more generous benefits improved healthcare utilisation [ 2 , 19 , 26 , 27 ]. This finding closely parallels existing empirical studies on URBMI and NRCMS [ 7 , 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that UEBMI, URBMI, and NRCMS had higher healthcare utilisation and experienced faster increases than uninsured respondents between 2008 and 2018. This implies that the rapid expansion of UEBMI, URBMI, and NRCMS with more generous benefits improved healthcare utilisation [ 2 , 19 , 26 , 27 ]. This finding closely parallels existing empirical studies on URBMI and NRCMS [ 7 , 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence has shown that the catastrophic health expenditure rate of those covered by NRCMS has increased significantly more than people covered by UEBMI and URBMI from 2000 to 2020 [ 39 ]. There are disparities in catastrophic health expenditure and impoverishment due to health expenditure among population income levels, and low-income households still have a higher chance of suffering financial hardship than high-income households [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this status quo are complex. In China, the benefit is determined by the level of funding in different health insurances, and the UEBMI, the scheme with the highest financial support, has relatively better service benefits and financial protection [46]. As mentioned earlier, the service benefits package of the URBMI and NRCMS initially focused on inpatient services.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the incomes of Chinese urban and rural residents are very different. The government needs to consider how to set an acceptable premium rate during the transition period to facilitate participants participating in the insurance according to their economic status, and to subsidize vulnerable groups so that everyone can enjoy the right to health [46]. Finally, improving the poor interconnection caused by the separation of health insurance management agencies is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that China’s policy interventions strongly promote the development of internet hospitals in China. Political commitment, sustainable financial sources, and administrative capacity are strong driving factors for achieving universal health coverage (UHC) through health insurance reform [ 26 ].…”
Section: Literature Viewmentioning
confidence: 99%